Diene-based block copolymer, diene-based block copolymer latex, diene-based block copolymer latex composition, and molded article

The diene-based block copolymer, with specific polymer blocks and heat treatment, addresses the challenge of achieving high tensile strength and low modulus in molded bodies without vulcanizing agents, resulting in flexible, heat-resistant coatings.

JP7665370B2Active Publication Date: 2025-04-21DENKA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021049143
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-04-21
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Conventional latex containing diene-based block copolymers fail to achieve molded bodies with low modulus and high tensile strength without using vulcanizing agents and accelerators, which are allergenic and costly.

Method used

A diene-based block copolymer comprising a polymer block (A) with a glass transition temperature of 80°C or higher and a diene-based polymer block (B), where the copolymer is heat-treated at 130°C for 30 minutes to achieve a tensile strength of 14 MPa or higher without the use of vulcanizing agents or accelerators.

Benefits of technology

The solution enables the production of immersion-forming coatings with excellent flexibility, tensile properties, and heat-aging resistance, while eliminating the use of allergenic vulcanizing agents and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665370000001
    Figure 0007665370000001
  • Figure 0007665370000002
    Figure 0007665370000002
  • Figure 0007665370000003
    Figure 0007665370000003
Patent Text Reader

Abstract

To provide: a diene-based block copolymer, a diene-based block copolymer latex, and a diene-based block copolymer latex composition, which can provide a dip-molded film having excellent flexibility, tensile characteristics, and thermal aging resistance even when amounts of use of a vulcanizer and a vulcanization accelerator are reduced or when these are not used; and a molded body having excellent flexibility, tensile characteristics, and thermal aging resistance even when amounts of use of a vulcanizer and a vulcanization accelerator are reduced or when these are not used.SOLUTION: The present invention provides a diene-based block copolymer comprising a polymer block (A) and a diene-based polymer block (B). The diene-based block copolymer contains, when the diene-based block copolymer is set to 100 mass%, 5-30 mass% of the polymer block (A) and 70-95 mass% of the diene-based polymer block (B). The polymer block (A) contains a monomer unit derived from a monomer which, when homopolymerized, can provide a polymer with a glass transition temperature of 80°C or higher. The diene-based block copolymer has tensile strength at break of 14 MPa or more when a film, obtained by dip-molding a diene-based block copolymer latex comprising the diene-based block copolymer, is subjected to a measurement according to JIS K 6251 after heat-treating the film at 130°C for 30 minutes.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a diene-based block copolymer, a diene-based block copolymer latex, a diene-based block copolymer latex composition, and a molded article. [Background technology]

[0002] Natural rubber (NR), isoprene rubber (IR), and CR gloves are widely used as surgical gloves. NR and IR gloves have low modulus and excellent texture, but NR gloves have type I allergy caused by latex proteins, and IR gloves have type IV allergy caused by vulcanization accelerator di-o-tolylguanidine (DOTG), etc., which are issues, and allergy-free alternative materials are desired. CR gloves do not contain latex proteins or DOTG, but they have issues with the modulus increasing and the texture deteriorating after product storage due to the influence of vulcanization accelerator zinc dibutyldithiocarbamate (ZDBC) that remains unreacted during vulcanization. In addition, in order to obtain the desired mechanical strength of diene rubber compositions, it has been necessary to use vulcanizing agents such as sulfur, zinc oxide, and magnesium oxide, and vulcanization accelerators such as thiuram, dithiocarbamate, thiourea, guanidine, xanthogenate, and thiazole. Since vulcanization accelerators are causative substances of type IV allergies that cause skin diseases such as dermatitis, reducing or eliminating the use of vulcanization accelerators has become an important theme. In addition, since eliminating the use of vulcanization accelerators leads not only to a reduction in allergies but also to cost reduction, a rubber composition that exhibits sufficient mechanical strength without using vulcanization accelerators is desired.

[0003] As a technique related to a latex containing a diene block copolymer, Patent Document 1 discloses an invention related to an aqueous dispersion containing a block copolymer containing a polymer block consisting of a monovinylidene aromatic monomer and a polymer block consisting of a conjugated diene. Patent Document 2 discloses a method for producing a block copolymer, which comprises continuously contacting at least one monovinylarene monomer, an organic monoalkali metal initiator, and at least one conjugated diene monomer under polymerization conditions, and then bonding them with a multifunctional coupling agent to form a block copolymer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-192869 A [Patent Document 2] Japanese Patent Application Publication No. 9-169825 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, there has been a demand for a latex which is allergy-free and capable of obtaining a molded article having low modulus and high tensile strength even when the amount of a vulcanizing agent and a vulcanization accelerator used is reduced or without using these agents. However, the latex containing a conventional diene block copolymer cannot obtain a molded article having low modulus and high tensile strength without using a vulcanizing agent and a vulcanization accelerator.

[0006] Therefore, an object of the present invention is to provide a diene-based block copolymer, a diene-based block copolymer latex, and a diene-based block copolymer latex composition which can provide a dip-molded coating excellent in flexibility, tensile properties, and heat aging resistance even when the amounts of a vulcanizing agent and a vulcanization accelerator used are reduced or even when they are not used, and to provide a molded article excellent in flexibility, tensile properties, and heat aging resistance even when the amounts of a vulcanizing agent and a vulcanization accelerator used are reduced or even when they are not used. [Means for solving the problem]

[0007] According to the present invention, there is provided a diene-based block copolymer comprising a polymer block (A) and a diene-based polymer block (B), the diene-based block copolymer comprising 5 to 30 mass % of the polymer block (A) and 70 to 95 mass % of the diene-based polymer block (B) when the diene-based block copolymer is taken as 100 mass %, the polymer block (A) comprises a monomer unit derived from a monomer which gives a polymer having a glass transition temperature of 80°C or higher upon homopolymerization, and the diene-based block copolymer has a tensile strength at break of 14 MPa or more as measured in accordance with JIS K 6251 after a coating obtained by dip-molding a diene-based block copolymer latex comprising the diene-based block copolymer is heat-treated at 130°C for 30 minutes.

[0008] The present inventors have conducted intensive studies and have found that, in a diene-based block copolymer containing a polymer block (A) and a diene-based polymer block (B), by specifying the type of polymer block (A) and the blending amounts of polymer block (A) and polymer block (B) and adjusting the diene-based block copolymer so that the strength of a coating obtained by dip molding a diene-based block copolymer latex containing the diene-based block copolymer is at least a certain level, a diene-based block copolymer can be obtained that can provide a dip-molded coating having excellent flexibility, tensile properties, and heat aging resistance even when the amounts of vulcanizing agents and vulcanization accelerators used are reduced or even when these are not used, which was difficult with conventional diene-based block copolymers, and have thus completed the present invention.

[0009] Preferably, the polymer block (A) is a diene-based block copolymer containing at least one monomer unit selected from the group consisting of an aromatic vinyl monomer unit, a methyl methacrylate monomer unit, and an acrylonitrile monomer unit. Preferably, in the above-described diene block copolymer, the polymer block (A) has a number average molecular weight of 10,000 or more. Preferably, the polymer block (B) is the above-described diene-based block copolymer having a diene-based monomer unit and a polyfunctional monomer unit. Preferably, the diene polymer block (B) is the diene block copolymer described above, which contains 0.05 to 10 mass % of the polyfunctional monomer unit when the diene polymer block (B) is taken as 100 mass %. Preferably, the polyfunctional monomer is the monomer represented by formula (1), the diene block copolymer described above, which contains an aromatic polyene monomer.

[0010] [ka] (In chemical formula (1), R 1 and R 2 Each independently represents hydrogen, chlorine, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted aryl group, a mercapto group, or a substituted or unsubstituted heterocyclyl group. W 1 represents a saturated or unsaturated hydrocarbon group, a saturated or unsaturated cyclic hydrocarbon group, or a saturated or unsaturated hydrocarbon group or cyclic hydrocarbon group containing a hetero atom. 1 is oxygen, sulfur or -NR 0 - represents the structure represented by R 0 represents hydrogen, chlorine, or a substituted or unsubstituted alkyl group, alkenyl group, aryl group, mercapto group, or heterocyclyl group.

[0011] According to another aspect of the present invention, there is provided a diene-based block copolymer latex comprising the diene-based block copolymer described above. Preferably, the diene block copolymer latex contains 20 to 100% by mass of a toluene insoluble matter relative to 100% by mass of the diene block copolymer latex. Preferably, the diene block copolymer latex has an average particle size of 300 nm or less as measured by dynamic light scattering. Preferably, the diene-based block copolymer latex is the above-mentioned diene-based block copolymer latex for use in a dip-molded article.

[0012] According to another aspect of the present invention, there is provided a diene-based block copolymer latex composition comprising the diene-based block copolymer latex described above. Preferably, the diene-based block copolymer latex composition described above is a diene-based block copolymer latex composition, in which the total content of the vulcanizing agent and the vulcanization accelerator is 5 mass% or less when the diene-based block copolymer latex contained in the diene-based block copolymer latex composition is 100 mass%. According to another aspect of the present invention, there is provided a molded article comprising the diene-based block copolymer latex composition described above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below by illustrating the embodiments of the present invention. The present invention is not limited by these descriptions. The various features of the embodiments of the present invention described below can be combined with each other. In addition, each feature can be an invention independently. In this specification and claims, the expression "A to B" means A or more and B or less.

[0014] 1. Diene block copolymer The diene block copolymer according to the present invention is a block copolymer containing a polymer block (A) derived from a monomer that, when homopolymerized, gives a polymer having a glass transition temperature of 80° C. or higher, and a diene polymer block (B) containing a diene monomer. The diene block copolymer also includes those having a structure in which block copolymers are chemically bonded to each other.

[0015] 1.1 Polymer block (A) The polymer block (A) is a polymer block derived from a monomer that can give a polymer having a glass transition temperature of 80° C. or more when homopolymerized. By using such a monomer, the tensile strength at break of the resulting diene block copolymer is improved. It is preferable to use a monomer that can give a polymer having a glass transition temperature of 85° C. or more. From the viewpoint of moldability, a monomer that can give a polymer having a glass transition temperature of 150° C. or less is preferable, and a monomer that can give a polymer having a glass transition temperature of 120° C. or less is particularly preferable. The glass transition temperature is, for example, 80, 85, 90, 95, 100, 105, 110, 120, 130, 140, or 150° C., and may be within a range between any two of the values ​​exemplified here. In this specification, the glass transition temperature is the extrapolated glass transition end temperature (T eg) measured in accordance with JIS K 7121. When the polymer block (A) is a polymer block obtained by polymerizing a monomer (A), the monomer (A) is preferably a monomer that, when the monomer A is homopolymerized to give a homopolymer (A) having a number average molecular weight of 10,000 to 30,000, has the above-mentioned glass transition temperature.

[0016] Examples of monomer units constituting the polymer block (A) include aromatic vinyl monomer units, methyl methacrylate monomer units, and acrylonitrile monomer units. Preferably, units derived from aromatic vinyl monomers are used, and styrene units are preferably used. The polymer block (A) may be a polymer block obtained by copolymerization of these monomers, or a polymer block composed of monomer units copolymerizable with these monomers, within the scope of the present invention.

[0017] The number average molecular weight of the polymer block (A) is preferably 10,000 or more from the viewpoint of the tensile properties and moldability of the resulting diene block copolymer. The number average molecular weight of the polymer block (A) can be, for example, 10000, 15000, 20000, 25000, or 30000, and may be within a range between any two of the numerical values ​​exemplified here. In addition, the molecular weight distribution of the polymer block (A) is preferably 2.0 or less from the viewpoint of moldability. The molecular weight distribution of the polymer block (A) can be, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0, and may be within a range between any two of the numerical values ​​exemplified here. In this specification, the number average molecular weight and the weight average molecular weight are values ​​calculated in terms of polystyrene measured by gel permeation chromatography (GPC) under the measurement conditions described below. Device name: HLC-8320 (Tosoh Corporation) Column: 3 TSKgel GMHHR-H in series Temperature: 40℃ Detection: Differential refractive index Solvent: Tetrahydrofuran Calibration curve: Prepared using standard polystyrene (PS).

[0018] 1.2 Diene polymer block (B) The diene polymer block (B) contains diene monomer units and is mainly composed of diene monomers. The diene polymer block (B) may contain polyfunctional monomer units. Furthermore, within the scope of the present invention, the diene polymer block (B) may be a polymer block containing diene monomer units, polyfunctional monomer units, and units derived from monomers copolymerizable therewith. When the diene polymer block (B) is taken as 100% by mass, the diene polymer block (B) preferably contains 90% by mass or more of structural units derived from diene monomers.

[0019] The content of each structural unit in the diene polymer block (B) is not particularly limited, but is preferably 90 to 99.95 mass% of diene monomer units and 0.05 to 10 mass% of polyfunctional monomer units. The content of the polyfunctional monomer units in the diene polymer block (B) is, for example, 0.05, 0.50, 1.00, 2.00, 3.00, 4.00, 5.00, 6.00, 7.00, 8.00, 9.00, or 10.00 mass%, and may be within a range between any two of the numerical values ​​exemplified here.

[0020] 1.2.1 Diene monomers Examples of the diene monomer according to one embodiment of the present invention include conjugated diene monomers having 4 to 6 carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. In the diene polymer block (B) according to one embodiment of the present invention, the content of the chloroprene monomer unit can be 50% by mass or less, 30% by mass or less, or 10% by mass or less, when the diene polymer block (B) is taken as 100% by mass. In addition, the diene polymer block (B) according to one embodiment of the present invention can be one that does not contain chloroprene. By setting the content of the chloroprene monomer unit to a certain level or less, it is possible to suppress the generation of hydrogen chloride under conditions of 100° C. or more, and the generation of hydrogen chloride and dioxins during incineration / combustion. In addition, the diene monomer according to one embodiment of the present invention is more preferably 1,3-butadiene or isoprene, and particularly preferably 1,3-butadiene. By including butadiene, it is possible to adjust the specific gravity of the polymer to be higher. From another perspective, butadiene, which is a liquefied gas, is less likely to leave unpolymerized monomers than chloroprene, which is a liquid.

[0021] 1.2.2 Polyfunctional monomers The polyfunctional monomer is used to improve the tensile properties and heat aging resistance of the dip-molded coating obtained. The polyfunctional monomer is a compound having two or more radical polymerizable groups in the molecule. From the viewpoints of flexibility, tensile strength at break, and moldability of the dip-molded coating obtained, a monomer represented by chemical formula (1) and an aromatic polyene monomer are preferably used. As the monomer represented by chemical formula (1), 1.9-nonanediol dimethacrylate, 1.9-nonanediol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, 1.6-hexanediol dimethacrylate, 1.6-hexanediol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate are particularly preferably used. The aromatic polyene monomer is an aromatic polyene having 10 or more and 30 or less carbon atoms and having a plurality of double bonds (vinyl groups) and one or more aromatic groups. Examples of the aromatic polyene monomer include units derived from aromatic polyene monomers such as o-divinylbenzene, p-divinylbenzene, m-divinylbenzene, 1,4-divinylnaphthalene, 3,4-divinylnaphthalene, 2,6-divinylnaphthalene, 1,2-divinyl-3,4-dimethylbenzene, and 1,3-divinyl-4,5,8-tributylnaphthalene. Preferably, one or a mixture of two or more of ortho-divinylbenzene units, para-divinylbenzene units, and meta-divinylbenzene units is suitably used.

[0022] [ka] (In chemical formula (1), R 1 and R 2 Each independently represents hydrogen, chlorine, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted aryl group, a mercapto group, or a substituted or unsubstituted heterocyclyl group. W 1represents a saturated or unsaturated hydrocarbon group, a saturated or unsaturated cyclic hydrocarbon group, or a saturated or unsaturated hydrocarbon group or cyclic hydrocarbon group containing a hetero atom. 1 is oxygen, sulfur or -NR 0 - represents the structure represented by R 0 represents hydrogen, chlorine, or a substituted or unsubstituted alkyl group, alkenyl group, aryl group, mercapto group, or heterocyclyl group.

[0023] 1.3 Content of each structural unit of diene block copolymer The content of each structural unit in the diene block copolymer is 5-30% by mass for polymer block (A) and 70-95% by mass for diene polymer block (B), preferably 5-15% by mass for polymer block (A) and 85-95% by mass for diene polymer block (B). When the polymer block (A) is 5% by mass or more, the tensile strength at break of the obtained diene block copolymer is improved. When the polymer block (A) is 30% by mass or less, the flexibility of the obtained diene block copolymer is improved. The polymer block (A) is preferably 15% by mass or less. When the diene polymer block (B) is 70% by mass or more, the flexibility of the obtained diene block copolymer is improved. The diene polymer block (B) is preferably 85% by mass or more. When the diene polymer block (B) is 95% by mass or less, the tensile strength at break of the obtained diene block copolymer is improved. When the diene block copolymer is taken as 100% by mass, the content of the polymer block (A) contained in the diene block copolymer is, for example, 5, 10, 15, 20, 25, or 30% by mass, and may be within a range between any two of the numerical values ​​exemplified here. The diene block copolymer according to one embodiment of the present invention may contain polymer blocks other than the polymer block (A) and the polymer block (B) within a range that does not impair the object of the present invention. When the diene block copolymer is taken as 100% by mass, the total content of the polymer block (A) and the polymer block (B) is preferably 80% by mass or more, and more preferably 90% by mass or more. The diene block copolymer according to one embodiment of the present invention may be composed of a polymer block (A) and a polymer block (B), or may not contain any other polymer block. The diene block copolymer may be a diblock copolymer of polymer block (A)-polymer block (B), which is composed of polymer block (A) and polymer block (B).

[0024] 1.4 Molecular weight of diene block copolymer The weight average molecular weight of the diene block copolymer is not particularly limited, but from the viewpoint of moldability, it is preferably from 50,000 to 600,000, and particularly preferably from 100,000 to 500,000.

[0025] 1.5 Method for producing diene block copolymer The method for producing the diene block copolymer according to the present invention will be described. The polymerization method is not particularly limited, and the copolymer can be produced by a known method such as solution polymerization, emulsion polymerization, or bulk polymerization, but emulsion polymerization is preferable for obtaining the desired diene block copolymer.

[0026] The polymerization method is not particularly limited as long as the desired diene-based block copolymer can be obtained, but the copolymer can be produced by a two-stage polymerization process consisting of polymerization step 1 for synthesizing polymer block (A) followed by polymerization step 2 for synthesizing diene-based polymer block (B).

[0027] (Polymerization step 1) The polymerization step 1 will be specifically described. In the polymerization step 1, the monomers constituting the polymer block (A) are subjected to living radical emulsion polymerization to synthesize the polymer block (A). The polymer block (A) obtained here preferably has the above-mentioned glass transition temperature. The emulsifier used in the emulsion polymerization is not particularly limited, but an anionic or nonionic emulsifier is preferable from the viewpoint of emulsion stability. In particular, it is preferable to use an alkali metal salt of rosin acid because it can provide an appropriate strength to the obtained diene block copolymer and prevent excessive shrinkage and breakage. From the viewpoint of efficient polymerization reaction, the concentration of the emulsifier is preferably 5 to 50% by mass relative to 100% by mass of the monomers constituting the polymer block (A). As the radical polymerization initiator, a known radical polymerization initiator can be used, for example, potassium persulfate, benzoyl peroxide, hydrogen peroxide, azo-based compounds, etc. can be used. The amount of pure water added is preferably 100 to 300% by mass relative to 100% by mass of the monomers constituting the polymer block (A). When the amount of pure water added is 300% by mass or less, the toluene insoluble content of the obtained diene block copolymer falls within the above-mentioned specific numerical range, and the tensile strength at break is more likely to be improved. The polymerization temperature may be appropriately determined depending on the type of monomer, but is preferably 10 to 100°C, and particularly preferably 20 to 80°C.

[0028] (Polymerization step 2) In the polymerization step 2, pure water, an emulsifier, a diene monomer, and optionally a polyfunctional monomer are added to the latex containing the polymer block (A) obtained by the living radical emulsion polymerization in the polymerization step 1, and the latex containing the target diene block copolymer can be obtained by emulsion polymerization. The diene monomer may be added all at once or in portions. The polymerization temperature in the polymerization step 2 is preferably 10 to 50°C from the viewpoint of ease of polymerization control. The polymerization reaction is terminated by adding a polymerization terminator. Examples of the polymerization terminator include thiodiphenylamine, 4-tert-butylcatechol, and 2,2'-methylenebis-4-methyl-6-tert-butylphenol. Unreacted monomers after the emulsion polymerization can be removed by a conventional method such as reduced pressure distillation.

[0029] To the latex containing the diene block copolymer obtained in the polymerization step 2, a freezing stabilizer, an emulsion stabilizer, a viscosity modifier, an antiaging agent, a preservative, etc. may be added after polymerization as long as the object of the present invention is not impaired.

[0030] (Recovery process) The method for recovering the diene-based block copolymer from the latex containing the diene-based block copolymer is not particularly limited, and any known method can be used, such as a method of recovering the diene-based block copolymer by immersing the diene-based block copolymer in a coagulation liquid or a method of precipitating the diene-based block copolymer using a poor solvent such as methanol.

[0031] The diene block copolymer preferably has a functional group having a structure represented by the following chemical formula (2) or (3).

[0032] [ka] (In chemical formula (2), R 3 represents hydrogen, chlorine, or a substituted or unsubstituted alkyl group, alkenyl group, aryl group, mercapto group, or heterocyclyl group. [ka]

[0033] The terminal structure represented by the above chemical formula (2) or chemical formula (3) is introduced into a block copolymer by emulsion polymerization in the presence of a known RAFT agent. The compound leading to the structure represented by the above chemical formula (2) is not particularly limited, and general compounds can be used, such as dithiocarbamates and dithioesters. Specifically, benzyl 1-pyrrole carbodithioate (common name: benzyl 1-pyrrole dithiocarbamate), benzyl phenyl carbodithioate, 1-benzyl-N,N-dimethyl-4-aminodithiobenzoate, 1-benzyl-4-methoxydithiobenzoate, 1-phenylethyl imidazole carbodithioate (common name: 1-phenylethyl imidazole dithiocarbamate), benzyl-1-(2-pyrrolidinone) carbodithioate, etc. oate) (common name: benzyl-1-(2-pyrrolidinone)dithiocarbamate), benzyl phthalimidyl carbodithioate, (common name: benzyl phthalimidyl dithiocarbamate), 2-cyanoprop-2-yl-1-pyrrole carbodithioate, (common name: 2-cyanoprop-2-yl-1-pyrrole dithiocarbamate), 2-cyanobut-2-yl-1-pyrrole carbodithioate, (common name: 2-cyanobut-2-yl- 1-Pyrrole dithiocarbamate), benzyl-1-imidazole carbodithioate, (common name benzyl-1-imidazole dithiocarbamate), 2-cyanoprop-2-yl-N,N-dimethyldithiocarbamate, benzyl-N,N-diethyldithiocarbamate, cyanomethyl-1-(2-pyrrolidone)dithiocarbamate, 2-(ethoxycarbonylbenzyl)prop-2-yl-N,N-diethyldithiocarbamate, 1-phenyl nylethyl dithiobenzoate, 2-phenylprop-2-yl dithiobenzoate, 1-acetate-1-yl-ethyl dithiobenzoate, 1-(4-methoxyphenyl)ethyl dithiobenzoate, benzyl dithioacetate, ethoxycarbonylmethyl dithioacetate, 2-(ethoxycarbonyl)prop-2-yl dithiobenzoate, 2-cyanoprop-2-yl dithiobenzoate, tert-butyl dithiobenzoate, 2,4,4-Trimethylpent-2-yldithiobenzoate, 2-(4-chlorophenyl)-prop-2-yldithiobenzoate, 3-vinylbenzyldithiobenzoate, 4-vinylbenzyldithiobenzoate, benzyldiethoxyphosphinyldithioformate, tert-butyltrithioperbenzoate, 2-phenylprop-2-yl-4-chlorodithiobenzoate, naphthalene-1-carboxylic acid-1-methyl-1-phenyl-ethyl ester, 4-cyano-4-methyl-4-thiobenzylsulfanylbutyric acid, dibenzyltetrathioterephthalate, carboxymethyldithiobenzoate, poly(ethylene oxide) with dithiobenzoate end groups, poly(ethylene oxide) with 4-cyano-4-methyl-4-thiobenzylsulfanylbutyric acid end groups, 2-[(2-phenylethanethioyl)sulfanyl]propanoic acid, 2-[(2-phenylethanethioyl)sulfanyl]succinic acid Acid, potassium 3,5-dimethyl-1H-pyrazole-1-carbodithioate, cyanomethyl-3,5-dimethyl-1H-pyrazole-1-carbodithioate, cyanomethylmethyl-(phenyl)dithiocarbamate, benzyl-4-chlorodithiobenzoate, phenylmethyl-4-chlorodithiobenzoate, 4-nitrobenzyl-4-chlorodithiobenzoate, phenylprop-2-yl-4-chlorodithiobenzoate, 1-cyano 1-methylethyl-4-chlorodithiobenzoate, 3-chloro-2-butenyl-4-chlorodithiobenzoate, 2-chloro-2-butenyldithiobenzoate, benzyldithioacetate, 3-chloro-2-butenyl-1H-pyrrole-1-dithiocarboxylic acid, 2-cyanobutan-2-yl 4-chloro-3,5-dimethyl-1H-pyrazole-1-carbodithioate, cyanomethylmethyl(phenyl)carbamodithioate. Among these, benzyl 1-pyrrolecarbodithioate and benzylphenylcarbodithioate are particularly preferred.

[0034] The compound leading to the structure represented by the above chemical formula (3) is not particularly limited, and a general compound can be used, for example, 2-cyano-2-propyldodecyltrithiocarbonate, dibenzyltrithiocarbonate, butylbenzyltrithiocarbonate, 2-[[(butylthio)thioxomethyl]thio]propionic acid, 2-[[(dodecylthio)thioxomethyl]thio]propionic acid, 2-[[(butylthio)thioxomethyl]thio]succinic acid, 2-[[(dodecylthio)thioxomethyl]thio]succinic acid, 2-[[(dodecylthio)thioxomethyl]thio] ]-2-methylpropionic acid, 2,2'-[carbonothioylbis(thio)]bis[2-methylpropionic acid], 2-amino-1-methyl-2-oxoethylbutyl trithiocarbonate, benzyl 2-[(2-hydroxyethyl)amino]-1-methyl-2-oxoethyltrithiocarbonate, 3-[[[(tert-butyl)thio]thioxomethyl]thio]propionic acid, cyanomethyldodecyltrithiocarbonate, diethylaminobenzyltrithiocarbonate, dibutylaminobenzyltrithiocarbonate and other trithiocarbonates are particularly preferred. Among these, dibenzyltrithiocarbonate and butylbenzyltrithiocarbonate are particularly preferred.

[0035] The diene copolymer according to one embodiment of the present invention preferably has at least one of a structure derived from a polyfunctional monomer, a structure represented by chemical formula (2), and a structure represented by chemical formula (3).

[0036] 2. Diene block copolymer latex The diene block copolymer latex according to one embodiment of the present invention contains the diene block copolymer described above. The diene block copolymer latex according to one embodiment of the present invention is preferably used for a dip-molded product. The latex according to one embodiment of the present invention can be immersed in a coagulating liquid and molded to obtain a dip-molded product. The dip-molded product can be suitably used for gloves, balloons, catheters, boots, etc.

[0037] The latex of the present embodiment can be obtained by a method in which the liquid at the end of polymerization synthesized by emulsion polymerization described in the above-mentioned method for producing a diene-based block copolymer is used as a latex as it is, or a method in which a recovered diene-based block copolymer is forcibly emulsified using an emulsifier to obtain a latex, and the like. The method in which the liquid at the end of polymerization synthesized by emulsion polymerization is used as a latex as it is is preferable because a latex can be easily obtained.

[0038] 2.1 Toluene insolubles in diene block copolymer latex The diene block copolymer latex according to one embodiment of the present invention preferably contains 20 to 100% by mass of toluene insoluble matter, more preferably 70 to 100% by mass, based on 100% by mass of the diene block copolymer latex. When the toluene insoluble matter is equal to or more than the lower limit, the block copolymers contain a structure in which they are chemically bonded to each other, and therefore the tensile strength at break is thought to be improved. The toluene insoluble matter can be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by mass, and may be within a range between any two of the numerical values ​​exemplified here. In this specification, the toluene insoluble matter is calculated by dissolving a freeze-dried diene block copolymer-containing latex in toluene, centrifuging the mixture, separating the gel fraction using a 200-mesh wire net, and measuring the mass of the dried mixture, and then calculating the amount from the following formula. (Mass of solid obtained by separating and drying gel fraction) / (Mass of solid obtained by freeze-drying latex containing diene block copolymer)×100 The toluene-insoluble content can be adjusted by controlling the types and amounts of raw materials blended during polymerization of the diene block copolymer as well as the polymerization conditions, and by controlling the type and amount of polymer blocks, for example, the type and amount of polyfunctional monomer units, and the type, amount, and structure of functional groups derived from a RAFT agent or the like.

[0039] 2.2 Average particle size of diene block copolymer latex The average particle size of the diene block copolymer latex measured by dynamic light scattering is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less, from the viewpoint of mechanical stability of the latex. The lower limit can be, for example, 100 nm or more. The average particle size can be, for example, 100, 120, 140, 150, 160, 170, 180, 190, 200, 220, 240, 260, 280, or 300 nm, and may be within a range between any two of the numerical values ​​exemplified here. In this specification, the average particle size is the average particle size measured by dynamic light scattering and calculated by photon correlation spectroscopy. The average particle size can be adjusted by controlling the type and amount of the diene block copolymer latex blended and the production conditions, for example, by adjusting the stirring conditions during emulsion polymerization.

[0040] 2.3 Mechanical stability of diene block copolymer latex The mechanical stability of the diene block copolymer latex according to one embodiment of the present invention is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. The mechanical stability of the diene block copolymer latex can be evaluated by the measurement method described in the Examples. The mechanical stability can be adjusted by controlling the type and amount of the diene block copolymer latex and the production conditions, for example, by controlling the average particle size of the diene block copolymer latex.

[0041] 2.4 Tensile properties of diene block copolymer latex The diene block copolymer of the present embodiment can provide an unvulcanized dip-molded coating that does not contain a vulcanizing agent or a vulcanization accelerator and has a tensile strength at break of 14 MPa or more measured according to JIS K 6251 after heat-treating a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer for 30 minutes at 130°C. The unvulcanized dip-molded coating has flexibility and exhibits sufficient mechanical strength even without containing a vulcanizing agent or a vulcanization accelerator. The tensile strength at break is more preferably 15 MPa or more, even more preferably 16 MPa or more, even more preferably 17 MPa or more, and particularly preferably 20 MPa or more. The upper limit is not particularly limited, but is, for example, 30 MPa or less. The tensile strength at break may be, for example, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30 MPa, or may be within a range between any two of the values ​​exemplified herein.

[0042] The diene block copolymer according to one embodiment of the present invention has a tensile strength at break measured in accordance with JIS K 6251 after a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer is heat-treated at 30° C. for 30 minutes and then subjected to a heat aging test at 100° C. for 22 hours, preferably 14 MPa or more, more preferably 15 MPa or more, even more preferably 16 MPa or more, even more preferably 17 MPa or more, and particularly preferably 20 MPa or more. The upper limit is not particularly limited, but is, for example, 30 MPa or less.

[0043] Furthermore, the diene block copolymer of the present embodiment has an elongation at break of preferably 900% or more, more preferably 905% or more, and even more preferably 910% or more, as measured in accordance with JIS K 6251 after a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer is heat-treated at 130° C. for 30 minutes. The upper limit is not particularly limited, but is, for example, 1300% or less.

[0044] The diene block copolymer according to one embodiment of the present invention is a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer, which is then heat-treated at 30° C. for 30 minutes and then subjected to a heat aging test at 100° C. for 22 hours. The elongation at break measured in accordance with JIS K 6251 is preferably 900% or more, more preferably 905% or more, and even more preferably 910% or more. The upper limit is not particularly limited, but is, for example, 1300% or less.

[0045] The diene block copolymer of the present embodiment has a modulus at 500% elongation measured in accordance with JIS K 6251 after a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer is heat-treated at 130° C. for 30 minutes. The modulus is preferably 3.0 MPa or less, more preferably 2.9 MPa or less, and even more preferably 2.8 MPa or less. The lower limit is not particularly limited, but is, for example, 1.0 MPa or more.

[0046] The diene block copolymer according to one embodiment of the present invention is a dip-molded coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer, and then heat-treated at 30° C. for 30 minutes, and then subjected to a heat aging test at 100° C. for 22 hours. The modulus at 500% elongation measured in accordance with JIS K 6251 is preferably 3.0 MPa or less, more preferably 2.9 MPa or less, and even more preferably 2.8 MPa or less. The lower limit is not particularly limited, but is, for example, 1.0 MPa or more. The dip-molded coating can be obtained by the method described in the Examples, and the dip-molded coating can be obtained without using a vulcanizing agent or a vulcanization accelerator during molding.

[0047] The tensile strength at break, elongation at break, and modulus at 500% elongation of the dip-molded coating obtained by dip-molding a diene block copolymer latex containing a diene block copolymer can be adjusted by adjusting the content of polyfunctional monomer units contained in the diene polymer block (B) or the content of the diene polymer block (B) in the diene block copolymer, by changing the polymerization temperature or polymerization rate during polymerization of the diene polymer block (B) to adjust the toluene-insoluble content, or by adjusting the type and amount of functional groups introduced by polymerization in the presence of a RAFT agent described below.

[0048] The dip-molded coating obtained from the diene block copolymer latex of this embodiment may contain a vulcanizing agent or a vulcanization accelerator. When the dip-molded coating contains a vulcanizing agent and a vulcanization accelerator, the total content of the vulcanizing agent and the vulcanization accelerator can be 5% by mass or less, more preferably 1% by mass or less, and more preferably 0.1% by mass, based on 100% by mass of the diene block copolymer latex contained in the dip-molded coating. However, since the unvulcanized dip-molded coating has sufficient mechanical strength even without the vulcanizing agent and the vulcanization accelerator, it is preferable that the unvulcanized dip-molded coating does not contain the vulcanizing agent and the vulcanization accelerator from the viewpoint of reducing allergies and reducing costs.

[0049] 3. Diene-based block copolymer latex composition The diene-based block copolymer latex composition according to one embodiment of the present invention contains a diene-based block copolymer latex containing the diene-based block copolymer described above.

[0050] 3.2 Components contained in diene block copolymer latex composition The diene block copolymer latex composition according to the present embodiment contains a diene block copolymer. Raw materials other than the diene block copolymer are not particularly limited and can be appropriately selected according to the purpose and application. Examples of raw materials that can be contained in the latex composition / rubber composition containing the diene block copolymer include vulcanizing agents, vulcanization accelerators, fillers or reinforcing agents, plasticizers, processing aids and lubricants, antiaging agents, and silane coupling agents.

[0051] The latex composition of the present embodiment may contain a vulcanizing agent or a vulcanization accelerator. When the latex composition according to the present embodiment contains a vulcanizing agent and / or a vulcanization accelerator, the total content of the vulcanizing agent and the vulcanization accelerator can be 5% by mass or less, more preferably 1% by mass or less, and more preferably 0.1% by mass, based on the diene block copolymer latex contained in the diene block copolymer latex composition, when the latex composition is taken as 100% by mass. However, the latex composition containing the diene block copolymer of the present embodiment exhibits sufficient mechanical strength even without vulcanization. For this reason, it is preferable that the latex composition does not contain a vulcanizing agent or a vulcanization accelerator from the viewpoints of reducing allergies and reducing costs.

[0052] As the antiaging agent for improving heat resistance, a primary antiaging agent that traps radicals to prevent autoxidation and a secondary antiaging agent that renders hydroperoxide harmless, which are used in normal rubber applications, can be added. The antiaging agents can be added in a ratio of 0.1 to 10 parts by mass, preferably 2 to 5 parts by mass, per 100 parts by mass of the latex component in the latex composition. These antiaging agents can be used alone or in combination of two or more kinds. Examples of the primary antiaging agent include phenol-based antiaging agents, amine-based antiaging agents, acrylate-based antiaging agents, imidazole-based antiaging agents, carbamic acid metal salts, and waxes. Examples of the secondary antiaging agent include phosphorus-based antiaging agents, sulfur-based antiaging agents, and imidazole-based antiaging agents. Examples of antioxidants include, but are not limited to, N-phenyl-1-naphthylamine, alkylated diphenylamines, octylated diphenylamines, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, p-(p-toluenesulfonylamido)diphenylamine, N,N'-di-2-naphthyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, N-phenyl-N'-(3-methacryloyloxy-2-hydroxypropyl)-p-phenylenediamine, 1,1,3-tris-(2-methyl-4 ... 4,4'-butylidenebis-(3-methyl-6-t-butylphenol), 2,2-thiobis(4-methyl-6-t-butylphenol), 7-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, pentaerythritol-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate, 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy)-hydrocinnamide, 2,4-bis[(octylthio)methyl]-o-crylene 3,5-di-t-butyl-4-hydroxybenzyl-phosphonate-diethyl ester, tetrakis[methylene(3,5-di-t-butyl-4-hydroxyhydrocinnamate)]methane, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate and 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, tris(nonyl phenyl)phosphite, thionyl Tris(mixed mono- and di-nonylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, diphenyl monotridecyl phosphite, diphenyl isodecyl phosphite, diphenyl isooctyl phosphite, diphenyl nonylphenyl phosphite, triphenyl phosphite, tris(tridecyl)phosphite, triisodecyl phosphite, tris(2-ethylhexyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, tetraphenyldipropyl Diphenyl glycol diphosphite, tetraphenyltetra(tridecyl)pentaerythritol tetraphosphite, 1,1,3-tris(2-methyl-4-di-tridecylphosphite-5-t-butylphenyl)butane, 4,4'-butylidenebis-(3-methyl-6-t-butyl-di-tridecylphosphite), 2,2'-ethylidenebis(4,6-di-t-butylphenol)fluorophosphite, 4,4'-isopropylidene-diphenol alkyl (C12-C15)phosphite, cyclic neopentanetetraylbis(2,4-di-t-butylphenyl phosphite), cyclic neopentanetetraylbis(2,6-di-t-butyl-4-phenyl phosphite), cyclic neopentanetetraylbis(nonylphenyl phosphite), bis(nonylphenyl)pentaerythritol diphosphite, dibutyl hydrogen phosphite, distearyl pentaerythritol diphosphite and hydrogenated bisphenol A pentaerythritol phosphite polymer, 2-mercaptobenzimidazole, butylated reaction product of p-cresol and dicyclopentadiene, etc.

[0053] The latex composition can be produced in a conventional manner using known machines and devices.

[0054] 4. Molded body A molded article according to one embodiment of the present invention contains the above-mentioned diene-based block copolymer latex composition, and preferably consists of the above-mentioned diene-based block copolymer latex composition. The components that the molded article according to the embodiment of the present invention may contain are as described above for the diene block copolymer latex composition. The properties that the molded article according to the embodiment of the present invention may have are as described above for the tensile properties of the diene block copolymer latex. EXAMPLES

[0055] The present invention will be described below with reference to examples and comparative examples, but these are merely illustrative and do not limit the content of the present invention.

[0056] Example 1 (Polymerization step 1) Synthesis of polymer block (A-1) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2.

[0057] The sampled latex was mixed with a large amount of methanol to precipitate the resin, which was then filtered and dried to obtain a sample of polymer block (A-1). The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A) were determined from the obtained sample. The analysis results are shown in Table 1. The methods for measuring the "number average molecular weight," "molecular weight distribution," and "glass transition temperature" will be described later.

[0058] (Polymerization step 2) Synthesis of diene polymer block (B-1) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of 1,9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. 20 ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used to prepare a film for evaluation.

[0059] Using a part of the sampled latex, the average particle size of the latex and the mechanical stability of the latex were measured. The analysis results are shown in Table 1. The measurement method will be described later. The sampled latex was mixed with a large amount of methanol to precipitate the resin content, which was then filtered and dried to obtain a diene block copolymer sample. The contents (mass%) of the polymer block (A-1) and the diene polymer block (B-1) of the butadiene block copolymer were determined from the obtained sample by analysis. The analysis results are shown in Table 1. The measurement method will be described later. The toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1. The measurement method will be described later.

[0060] Example 2 (Polymerization step 1) Synthesis of polymer block (A-2) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 3333g of pure water, 160g of potassium disproportionated rosinate (Harima Chemicals), 26.0g of potassium hydroxide, 13.3g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 250g of styrene monomer, and 4.33g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 2.73g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-2) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0061] (Polymerization step 2) Synthesis of diene polymer block (B-2) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 5584 g of butadiene monomer and 114.0 g of 1.9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-2) and the diene polymer block (B-2) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0062] Example 3 (Polymerization step 1) Synthesis of polymer block (A-3) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 5733g of pure water, 275g of potassium disproportionated rosinate (Harima Chemicals), 44.7g of potassium hydroxide, 22.9g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 430g of styrene monomer, and 7.45g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 4.69g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-3) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0063] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-3) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 3094 g of butadiene monomer and 63.1 g of 1.9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-3) and the diene polymer block (B-3) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0064] Example 4 (Polymerization step 1) Synthesis of polymer block (A-4) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-4) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0065] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-4) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of 1.9-nonanediol diacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-4) and the diene polymer block (B-4) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0066] Example 5 (Polymerization step 1) Synthesis of polymer block (A-5) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-5) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0067] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-5) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of Light Ester EG (manufactured by Kyoeisha Chemical Co., Ltd.), which is ethylene glycol diacrylate, were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was made using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-5) and the diene polymer block (B-5) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0068] Example 6 (Polymerization step 1) Synthesis of polymer block (A-6) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-6) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0069] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-6) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 93.3 g of divinylbenzene were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-6) and the diene polymer block (B-6) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0070] Example 7 (Polymerization step 1) Synthesis of polymer block (A-7) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 5450g of pure water, 262g of potassium disproportionated rosinate (Harima Chemicals), 42.5g of potassium hydroxide, 21.8g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 2500g of styrene monomer, and 43.3g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 27.3g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-7) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0071] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-7) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 2732g of pure water, 131g of disproportionated potassium rosinate (Harima Chemicals), 21.3g of potassium hydroxide, 10.9g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), and 783g of latex containing the polymer block (A-7) produced in polymerization step 1 were charged, the internal temperature was set to 45°C, the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen, and the mixture was stirred at 200 rpm. Then, 3000g of butadiene monomer was slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, the polymerization was stopped by adding a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, and the unreacted butadiene monomer was removed by vacuum distillation. For the measurement of physical properties, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the contents (mass%) of the polymer block (A-7) and the diene polymer block (B-7) of the diene block copolymer were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0072] Example 8 (Polymerization step 1) Synthesis of polymer block (A-8) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-8) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0073] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-8) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of triallyl isocyanurate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-8) and the diene polymer block (B-8) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0074] Example 9 (Polymerization step 1) Synthesis of polymer block (A-9) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-9) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0075] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-9) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of hydroxypivalic acid neopentyl glycol acrylic acid adduct (manufactured by Kyoeisha Chemical Co., Ltd.) were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-9) and the diene polymer block (B-9) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0076] Example 10 (Polymerization step 1) Synthesis of polymer block (A-10) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of potassium disproportionated rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-10) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0077] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-10) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4480 g of butadiene monomer and 91.4 g of trimethylolpropane triacrylate (Kyoeisha Chemical Co., Ltd.) were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-10) and the diene polymer block (B-10) of the diene block copolymer were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0078] Example 11 (Polymerization step 1) Synthesis of polymer block (A-11) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 6667g of pure water, 320g of disproportionated potassium rosinate (Harima Chemicals), 52.0g of potassium hydroxide, 26.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 500g of styrene monomer, and 6.50g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 4.09g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-11) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0079] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-11) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 1607 g of butadiene monomer and 32.8 g of 1,9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-11) and the butadiene polymer block (B-11) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0080] Example 12 (Polymerization step 1) Synthesis of polymer block (A-12) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 5450g of pure water, 262g of potassium disproportionated rosinate (Harima Chemicals), 42.5g of potassium hydroxide, 21.8g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 2500g of styrene monomer, and 32.5g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 20.5g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-12) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0081] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-12) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 1188g of pure water, 57g of disproportionated potassium rosinate (Harima Chemicals), 9.3g of potassium hydroxide, 4.8g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), and 3147g of latex containing the polymer block (A-12) produced in polymerization step 1 were charged, the internal temperature was set to 45°C, the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen, and the mixture was stirred at 200 rpm. Then, 3000g of butadiene monomer was slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, the polymerization was stopped by adding a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, and the unreacted butadiene monomer was removed by vacuum distillation. For the measurement of physical properties, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-12) of the diene block copolymer and the butadiene polymer block (B-12) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0082] (Example 13) (Polymerization step 1) Synthesis of polymer block (A-13) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of disproportionated potassium rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of methyl methacrylate monomer, and 4.14g of butyl-2-cyanoisopropyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 2.87g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-13) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0083] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-13) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4424 g of butadiene monomer and 90.3 g of 1.9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-13) and the butadiene polymer block (B-13) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0084] Comparative Example 1 (Polymerization step 1) Synthesis of polymer block (A-14) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 3067g of pure water, 147g of potassium disproportionated rosinate (Harima Chemicals), 23.9g of potassium hydroxide, 12.3g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 230g of styrene monomer, and 3.99g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 2.51g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-14) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0085] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-14) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 7278 g of butadiene monomer and 148.5 g of 1.9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-14) and the butadiene polymer block (B-14) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0086] Comparative Example 2 (Polymerization step 1) Synthesis of polymer block (A-15) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 6667g of pure water, 320g of potassium disproportionated rosinate (Harima Chemicals), 52.0g of potassium hydroxide, 26.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 500g of styrene monomer, and 4.27g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 2.69g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization process 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-15) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0087] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-15) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 1607 g of butadiene monomer and 32.8 g of 1.9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-15) and the butadiene polymer block (B-15) of the diene block copolymer were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0088] Comparative Example 3 Synthesis of copolymers containing only butadiene-based polymer blocks (B-16) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 3600g of pure water, 175g of disproportionated potassium rosinate (Harima Chemicals), 28.4g of potassium hydroxide, 16.0g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 4000g of butadiene monomer, 81.6g of 1.9-nonanediol dimethacrylate, and 4.72g of butylbenzyl trithiocarbonate were charged, the internal temperature was set to 45°C, the internal pressure of the reactor was increased to 0.6MPaG using nitrogen, and the mixture was stirred at 200 rpm. 2.96g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For the measurement of physical properties, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex and the mechanical stability of the latex were determined by analysis in the same manner as in Example 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0089] Comparative Example 4 (Polymerization step 1) Synthesis of polymer block (A-17) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4616g of pure water, 206g of potassium disproportionated rosinate (Harima Chemicals), 2.3g of potassium hydroxide, 46.2g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 462g of styrene monomer, and 9.2g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 6.0g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization step 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-16) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0090] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-17) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4154 g of butadiene monomer was slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-17) and the butadiene polymer block (B-17) of the diene block copolymer were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0091] Comparative Example 5 (Polymerization step 1) Synthesis of polymer block (A-18) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4616g of pure water, 206g of potassium disproportionated rosinate (Harima Chemicals), 2.3g of potassium hydroxide, 46.2g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 692g of styrene monomer, and 9.2g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 6.0g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in polymerization process 2. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-18) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1.

[0092] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-18) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 3924 g of butadiene monomer was slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. For physical property measurement, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the polymer block (A-18) and the butadiene polymer block (B-18) of the diene block copolymer were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 1. In addition, the toluene insoluble matter was determined from the sampled latex. The analysis results are shown in Table 1.

[0093] Comparative Example 6 Synthesis of triblock copolymers (Synthesis of the first block) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4613g of pure water, 204.4g of potassium disproportionated rosinate (Harima Chemicals), 2.3g of potassium hydroxide, 46.1g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 230g of styrene monomer, and 9.2g of benzyl 1-pyrrole carbodithioate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 6.0g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. 20ml of the obtained latex was sampled for physical property measurement, and the remaining latex was used in the next polymerization step. The number average molecular weight, molecular weight distribution, and glass transition temperature of the first block were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 2. (Synthesis of the second block) After the synthesis of the first block, the nitrogen gas flow was stopped when the internal temperature dropped to 45°C, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 4424 g of butadiene monomer was added and polymerization was carried out. When the polymerization rate of the butadiene monomer reached 80%, a 10 mass% aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, was added to terminate the polymerization, and the unreacted butadiene monomer was removed by distillation under reduced pressure. The obtained latex was used in the next polymerization step. (Synthesis of the third block) After the synthesis of the second block, the internal temperature was raised to 80°C, 230g of styrene monomer was charged, and 6.0g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name: VA-044) was added as a polymerization initiator to start polymerization. After polymerization, the mixture was cooled to 25°C to terminate polymerization. For physical property measurement, 20ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the styrene block, which is the first block and the third block of the synthesized triblock copolymer, and the butadiene block, which is the second block, and the toluene insoluble content were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 2.

[0094] Comparative Example 7 Preparation of a mixture of homopolymers of polymer block (A) and homopolymers of butadiene-based polymer block (B) (Synthesis of homopolymer of polymer block (A)) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4666g of pure water, 224g of disproportionated potassium rosinate (Harima Chemicals), 36.4g of potassium hydroxide, 18.7g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 350g of styrene monomer, and 6.07g of butylbenzyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 3.82g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]2hydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. When the polymerization rate of the styrene monomer reached 95%, the polymerization was stopped by adding a 10% by mass aqueous solution of N,N-diethylhydroxylamine as a polymerization terminator. 20 ml of the obtained latex was sampled for measuring physical properties. The number average molecular weight, molecular weight distribution and glass transition temperature of the homopolymer of the polymer block (A) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 3.

[0095] (Synthesis of homopolymer of butadiene-based polymer block (B)) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 3960g of pure water, 193g of disproportionated potassium rosinate (Harima Chemicals), 31.2g of potassium hydroxide, 17.6g of sodium salt of β-naphthalenesulfonic acid formalin condensate (Kao Corporation, product name: Demol N), 4400g of butadiene monomer, 89.8g of 1.9-nonanediol dimethacrylate, and 5.19g of butylbenzyl trithiocarbonate were charged, the internal temperature was set to 45°C, the internal pressure of the reactor was increased to 0.6MPaG using nitrogen, and the reaction vessel was stirred at 200 rpm. 3.26g of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrogen chloride (Fujifilm Wako Pure Chemical Industries, product name: VA-044) was added as a polymerization initiator to start polymerization. When the polymerization rate of the butadiene monomer reached 80%, the polymerization was terminated by adding a 10% by mass aqueous solution of N,N-diethylhydroxylamine, which is a polymerization terminator, and the unreacted butadiene monomer was removed by distillation under reduced pressure.

[0096] (Mixing of homopolymer latex of polymer block (A) and homopolymer latex of butadiene-based polymer block (B)) 4000 g of the obtained homopolymer latex of the polymer block (A) and 4000 g of the homopolymer latex of the butadiene-based polymer block (B) were charged into a 10 L capacity autoclave equipped with a stirrer and a heating / cooling jacket, and the inside temperature was set to 45° C. and stirred at 200 rpm. For physical property measurement, 20 ml of the obtained latex was sampled, and the remaining latex was used to prepare a film for evaluation. The average particle size of the latex, the mechanical stability of the latex, and the contents (mass%) of the homopolymer of the polymer block (A) and the homopolymer of the butadiene-based polymer block (B) in the polymer obtained by mixing, and the toluene insoluble content were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 3.

[0097] ( Example 14 ) Synthesis of diene block copolymer latexes by forced emulsification method. (Polymerization step 1) Synthesis of polymer block (A-19) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4616g of tetrahydrofuran, 87.5g of styrene monomer, and 1.5g of benzyl butyl trithiocarbonate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 0.49g of azobisisobutyronitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name: AIBN) was added as a polymerization initiator to start polymerization. 20ml of the obtained solution was sampled for physical property measurement, and the remaining latex was used in the next polymerization step. The number average molecular weight, molecular weight distribution, and glass transition temperature of the polymer block (A-19) were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 4.

[0098] (Polymerization step 2) Synthesis of butadiene-based polymer block (B-19) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 1120 g of butadiene monomer and 22.8 g of 1,9-nonanediol dimethacrylate were slowly added over 2 hours to carry out polymerization. When the polymerization rate of the butadiene monomer reached 80%, the polymerization was terminated by adding a 10 mass% tetrahydrofuran solution of phenothiazine, which is a polymerization terminator, and the unreacted butadiene monomer and tetrahydrofuran were removed by vacuum distillation to obtain a diene block copolymer sample.

[0099] (Forced emulsification process) Forced emulsification of diene block copolymer 350 g of the diene block copolymer obtained in the polymerization step 2 was dissolved in 4200 g of benzene. 4725 g of pure water, 70 g of disproportionated potassium rosinate (manufactured by Harima Chemicals Co., Ltd.), 0.78 g of potassium hydroxide, and 1.4 g of sodium salt of β-naphthalenesulfonic acid formalin condensate (manufactured by Kao Corporation, product name: Demol N) were added to the obtained solution, and the mixture was forcedly emulsified using a homogenizer. Benzene and water were removed by distillation under reduced pressure so that the solid content concentration of the obtained latex was 50%, and a diene block copolymer latex was obtained. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, the content (mass%) of the polymer block (A-19) and the butadiene polymer block (B-19) of the diene block copolymer, and the toluene insoluble content were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 4.

[0100] Comparative Example 9 Synthesis of triblock copolymer latexes by forced emulsification method. (Synthesis of the first block) Polymerization was carried out using a 10L autoclave equipped with a stirrer and a jacket for heating and cooling. 4616g of tetrahydrofuran, 70g of styrene monomer, and 2.8g of benzyl 1-pyrrolecarbodithioate were charged, and the internal temperature was set to 80°C and stirred at 200 rpm under a nitrogen stream. 0.93g of azobisisobutyronitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name: AIBN) was added as a polymerization initiator to start polymerization. 20ml of the obtained solution was sampled for physical property measurement, and the remaining latex was used in the next polymerization step. The number average molecular weight, molecular weight distribution, and glass transition temperature of the first block were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 5. (Synthesis of the second block) After the polymerization step 1, when the internal temperature dropped to 45°C, the nitrogen gas flow was stopped, and the internal pressure of the reactor was increased to 0.6 MPaG using nitrogen. 1346 g of butadiene monomer was added and polymerization was carried out. When the polymerization rate of the butadiene monomer reached 80%, the polymerization was terminated by adding a 10 mass% tetrahydrofuran solution of phenothiazine, which is a polymerization terminator. (Synthesis of the third block) After the synthesis of the second block, the internal temperature was raised to 80°C, 70 g of styrene monomer was charged, and 0.93 g of azobisisobutyronitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., trade name: AIBN) was added as a polymerization initiator to start polymerization. After the polymerization, unreacted butadiene monomer and tetrahydrofuran were removed by reduced pressure distillation to obtain a triblock copolymer. (Forced emulsification process) Forced emulsification of triblock copolymer 350 g of the triblock copolymer obtained by the synthesis of the third block was dissolved in 4200 g of benzene. 4725 g of pure water, 70 g of disproportionated potassium rosinate (manufactured by Harima Chemicals Co., Ltd.), 0.78 g of potassium hydroxide, and 1.4 g of sodium salt of β-naphthalenesulfonic acid formalin condensate (manufactured by Kao Corporation, product name: Demol N) were added to the obtained solution, and forced emulsification was performed using a homogenizer. Benzene and water were removed by vacuum distillation so that the solid content concentration of the obtained latex was 50%, and a diene-based block copolymer latex was obtained. For physical property measurement, 20 ml of the obtained latex was sampled, and a film for evaluation was produced using the remaining latex. The average particle size of the latex, the mechanical stability of the latex, and the content (mass%) of the styrene block which is the first block and the third block of the synthesized triblock copolymer and the butadiene block which is the second block, and the toluene insoluble content were determined by analysis in the same manner as in Example 1. The analysis results are shown in Table 5.

[0101] [analysis] (Measurement of number average molecular weight and molecular weight distribution of polymer block (A)) The number average molecular weight and molecular weight distribution are values ​​calculated as polystyrene by gel permeation chromatography (GPC) and are values ​​measured under the measurement conditions described below. Device name: HLC-8320 (Tosoh Corporation) Column: 3 TSKgel GMHHR-H in series Temperature: 40℃ Detection: Differential refractive index Solvent: Tetrahydrofuran Calibration curve: Prepared using standard polystyrene (PS).

[0102] (Glass transition temperature of polymer block (A)) The glass transition temperature was measured using a differential scanning calorimeter in accordance with JIS K 7121 by the following method. Device name: DSC1 (Mettler Toledo) Procedure: Under a nitrogen flow of 50 ml / min, the sample was heated to 120°C at a rate of 10°C / min, kept at 120°C for 10 minutes, then cooled to -60°C. The sample was then heated to 120°C at a rate of 10°C / min to obtain a DSC curve. The glass transition temperature was determined as the temperature at the intersection of a straight line extending the base line on the high temperature side to the low temperature side and a tangent line drawn at the point where the slope of the curve on the high temperature side of the peak is maximum.

[0103] (Measurement of the content of polymer block (A) and butadiene polymer block (B) in diene block copolymer) The measurements were carried out using pyrolysis gas chromatogram and 1H-NMR as follows. Pyrolysis gas chromatogram Instrument name: HP5890-II Column: DB-5 0.25 mm diameter x 30 m (film thickness 1.0 μm) Column temperature: 50℃(5min)→10℃ / min→150℃→25℃ / min→300℃ Inlet temperature: 250℃ Detector temperature: 280℃ Detector: FID 1H-NMR device name: JNM-ECX-400 (manufactured by JEOL Ltd.) Procedure: A diene block copolymer consisting of a polymer block (A) and a butadiene polymer block (B) not containing a polyfunctional monomer unit was measured by pyrolysis gas chromatography, and a calibration curve was prepared from the area ratio of the peak derived from the polymer block (A) to the peak derived from the butadiene polymer block (B) and the contents of the polymer block (A) and the butadiene polymer block (B) in the diene block copolymer obtained by measuring 1H-NMR. A diene block copolymer sample precipitated by mixing the sampled latex with methanol was measured by pyrolysis gas chromatography, and the contents of the polymer block (A) and the butadiene polymer block (B) in the diene block copolymer were obtained from the area ratio of the peak derived from the polymer block (A) to the peak derived from the butadiene polymer block (B) using the calibration curve prepared above.

[0104] [Measurement of toluene insolubles] The latex obtained in the polymerization step 2 was freeze-dried, and 1 g of the solid was cut into 2 mm squares, placed in a conical beaker, and dissolved in toluene for 16 hours. After that, the mixture was centrifuged, and the gel fraction was separated using a 200 mesh wire net. The dried mass was measured, and the toluene insoluble fraction was calculated using the following formula. (Mass of solid obtained by separating and drying gel fraction) / (Mass of solid obtained by freeze-drying latex containing diene block copolymer)×100

[0105] (Measurement of average particle size of latex) 0.1 g of the sampled latex was dissolved in 50 g of pure water, and the sample was measured by dynamic light scattering using ELSZ-2 manufactured by Otsuka Electronics Co., Ltd., and the average particle size of the latex was calculated by photon correlation spectroscopy.

[0106] (Measurement of mechanical stability of latex) The mechanical stability of the latex was measured in accordance with JIS K 6392 using a Maron mechanical stability tester by the following method. Procedure: The sampled latex was filtered through a wire net to remove impurities, and then the filtered latex was adjusted to 20°C and 50g was weighed into a test container. The test container was attached to a tester and measured for 10 minutes with a load of 10kg. After the measurement, the sample in the test container was filtered through an 80-mesh wire net that had been dried at 125°C for 1 hour and cooled in a desiccator, and the 80-mesh wire net and precipitate were dried in a dryer at 125°C for 1 hour and then cooled in a desiccator, and the 80-mesh wire net and precipitate were weighed. The total solid content (unit: %) of the sampled latex was calculated in accordance with JIS K 6387. Next, the coagulation rate (unit: mass%) of the latex was calculated using the following formula. [(Mass of 80 mesh wire net and precipitate after drying (unit: g)) - (Mass of 80 mesh wire net (unit: g))] / [50 × ((Total solid content of latex (unit: mass%)) / 100)] × 100 The obtained coagulation rate of the latex was regarded as the mechanical stability of the latex. A latex mechanical stability of 1% by mass or less was regarded as an acceptable level.

[0107] [Preparation of samples for tensile tests] (Preparation of latex containing diene-based block copolymer) To 100 parts by mass (solid content equivalent) of the diene block copolymer in the latex obtained in the polymerization process 2, 2 parts by mass of a butylated reaction product of p-cresol and dicyclopentadiene (trade name "Nocrac PBK", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) as an antiaging agent, 0.3 parts by mass of sodium lauryl sulfate (trade name "EMAL 10", manufactured by Kao Corporation), and water were added to adjust the solid content concentration of the blend to 30% by mass, and the mixture was mixed at 20°C for 16 hours using a ceramic ball mill to prepare the blend. (Film Creation) A ceramic cylinder with an outer diameter of 50 mm was immersed for 1 second in a coagulation liquid containing 62 parts by mass of water, 35 parts by mass of potassium nitrate tetrahydrate, and 3 parts by mass of calcium carbonate, and then removed. After drying for 4 minutes, the cylinder was immersed for 2 minutes in the latex prepared above. The cylinder was then washed with running water at 45°C for 1 minute, and heated at 130°C for 30 minutes to remove moisture, producing a film (140 x 150 mm, thickness: 0.2 mm) for tensile testing.

[0108] [Evaluation of tensile properties] The prepared film was heat-treated at 130°C for 30 minutes, and then the modulus at 500% elongation, tensile strength at break, and elongation at break were measured in accordance with JIS K 6251. The pass level was determined to be 3.0 MPa or less for the modulus at 500% elongation, 14 MPa or more for the tensile strength at break, and 900% or more for the elongation at break.

[0109] [Evaluation of thermal aging properties] The prepared film was subjected to a heat aging test at 100°C for 22 hours in a forced circulation heat aging tester, and then the modulus at 500% elongation, tensile strength at break, and elongation at break were measured in accordance with JIS K 6251. A modulus at 500% elongation of 3.0 MPa or less, a tensile strength at break of 14 MPa or more, and an elongation at break of 900% or more were considered to be acceptable.

[0110] [Table 1] JPEG0007665370000006.jpg241127

[0111] [Table 2]

[0112] [Table 3]

[0113] [Table 4]

[0114] [Table 5]

Claims

1. A diene-based block copolymer comprising a polymer block (A) and a diene-based polymer block (B), The diene block copolymer has, when the diene block copolymer is taken as 100% by mass, The polymer block (A) is contained in an amount of 5 to 30% by mass, The diene polymer block (B) is contained in an amount of 70 to 95% by mass, The polymer block (A) contains a monomer unit derived from a monomer that, upon homopolymerization, gives a polymer having a glass transition temperature of 80° C. or higher, The diene polymer block (B) has a diene monomer unit and a polyfunctional monomer unit, The diene block copolymer has a tensile strength at break of 14 MPa or more as measured in accordance with JIS K 6251 after a coating obtained by dip-molding a diene block copolymer latex containing the diene block copolymer is heat-treated at 130° C. for 30 minutes (excluding the case where the diene polymer block (B) contains 90% by mass or more of structural units derived from chloroprene monomers when the diene polymer block (B) is taken as 100% by mass).

2. 2. The diene block copolymer according to claim 1, wherein the polymer block (A) contains at least one monomer unit selected from the group consisting of an aromatic vinyl monomer unit, a methyl methacrylate monomer unit, and an acrylonitrile monomer unit.

3. 3. The diene block copolymer according to claim 1, wherein the polymer block (A) has a number average molecular weight of 10,000 or more.

4. The diene-based block copolymer according to any one of claims 1 to 3, wherein the diene-based polymer block (B) contains the polyfunctional monomer unit in an amount of 0.05 to 10% by mass when the diene-based polymer block (B) is taken as 100% by mass.

5. The diene block copolymer according to any one of claims 1 to 4, wherein the polyfunctional monomer comprises a monomer represented by chemical formula (1) or an aromatic polyene monomer. 【Chemistry 1】 (In chemical formula (1), R 1 and R 2 each independently represents hydrogen, chlorine, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted aryl group, a mercapto group, or a substituted or unsubstituted heterocyclyl group. 1 represents a saturated or unsaturated hydrocarbon group, a saturated or unsaturated cyclic hydrocarbon group, or a saturated or unsaturated hydrocarbon group or cyclic hydrocarbon group containing a hetero atom. 1 is oxygen, sulfur or -NR 0 R represents a structure represented by the formula: 0 represents any one of hydrogen, chlorine, a substituted or unsubstituted alkyl group, alkenyl group, aryl group, mercapto group, and heterocyclyl group.)

6. A diene-based block copolymer latex comprising the diene-based block copolymer according to any one of claims 1 to 5.

7. The diene block copolymer latex according to claim 6, wherein the diene block copolymer latex contains 20 to 100% by mass of a toluene insoluble matter relative to 100% by mass of the diene block copolymer latex.

8. 8. The diene block copolymer latex according to claim 6, wherein the diene block copolymer latex has an average particle size of 300 nm or less as measured by a dynamic light scattering method.

9. The diene-based block copolymer latex according to any one of claims 6 to 8, which is for use in a dip-molded product.

10. A diene-based block copolymer latex composition comprising the diene-based block copolymer latex according to any one of claims 6 to 9.

11. The diene-based block copolymer latex composition according to claim 10, wherein a total content of a vulcanizing agent and a vulcanization accelerator is 5 mass% or less when the diene-based block copolymer latex contained in the diene-based block copolymer latex composition is 100 mass%.

12. A molded article comprising the diene-based block copolymer latex composition according to claim 10 or 11.

Citation Information

Patent Citations

  • Conjugated diene / monovinyl arene block copolymer, its production and polymer blend

    JP1997169825A

  • Block copolymer latex

    JP2003192869A

  • Olefinically unsaturated radial styrenic block copolymer and improved latex free of vulcanizing agents

    JP2016538360A

  • JPP7575447B

  • Block copolymer and method for producing block copolymer

    WO2018181801A1